2020
DOI: 10.1002/cbdv.201900484
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Biological and Chemical Investigation of Sixteen Achillea Species’ Essential Oils via Chemometric Approach

Abstract: Representatives of the Achillea genus are widely used as foods or nutraceuticals. Considering the increasing demand for herbal dietary supplements with health promoting effects, the objective of this research was to evaluate the chemical composition and biological activities of the essential oils obtained from sixteen Achillea species (A. biebersteinii, A. wilhelmsii subsp. wilhelmsii, A. aleppica subsp. zederbaueri, A. vermicularis, A. monocephala, A. nobilis, A. goniocephala, A. sintenisii, A. coarctata, A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…It was shown that these subspecies also reveal significant morphological differences [30]. The literature survey revealed a high variability of Achillea species essential oil profile [12,13,20,36]. Flavonoid and phenolic compounds were detected at varying concentrations across the analysed species (Table III).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that these subspecies also reveal significant morphological differences [30]. The literature survey revealed a high variability of Achillea species essential oil profile [12,13,20,36]. Flavonoid and phenolic compounds were detected at varying concentrations across the analysed species (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…The genus Achillea, generally known as "yarrow", belongs to the richest and youngest evolutionary genera of the Asteraceae family [28]. About 140 perennial herbaceous species with worldwide distribution have been recognized in this genus [36]. Numerous species of the genus have been used traditionally as antibacterial, anti-inflammatory, vermifuge, analgesic and expectorant etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it appears that when picking yarrow for its essential oils, all taxa are similarly suitable for collection. The composition of essential oils, which was not tested here, however, most probably differs among taxa (Yener et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Camphor and 1,8-cineole were found to be the main ingredients (8). In another study, the essential oil of this plant was analysed and high amount endo-borneol, eucalyptol and camphor were found (9).…”
Section: Introductionmentioning
confidence: 86%